Centralized Bargaining, Efficiency Wages, and Flexibility - Ramaswamy, Ramana (IMF Working Papers; Working Paper, 1993)
The main focus of the 'wage bargaining' literature has been on the factors promoting real wage flexibility at the macro level. This paper, in contrast, examines the microeconomic issues of wage bargaining. More specifically, this paper appraises the following questions: (a) what are the conditions under which a firm prefers decentralized to centralized bargaining?, (b) what are the characteristic features of firms which prefer decentralized to centralized bargaining?, and (c) has the proportion of firms which prefer decentralized bargaining increased over time? These questions are examined in an efficiency wage model with insider-outsider features. This paper provides useful theoretical insights for understanding the issues involved in shifting from centralized to decentralized wage bargaining.